Vernacular translation in Renaissance France, Spain, Portugal and Britain: a comparative survey. Issue 1 (February 2015) - Wilkinson, Alexander S.
<x xml:space="preserve">Abstract</x> Vernacular translations have, largely, failed to feature in our geography of the Renaissance book. This is a consequence both of our inclination towards a teleological approach to understanding past cultures as well as the priority we have placed on national narratives. Yet, if cultural communities experienced their own particular histories and developments, they were also interconnected. Within the book world, Latin allowed ideas to cross virtually all linguistic boundaries, while vernacular multilingualism was by no means uncommon. Printed vernacular translations, too, played a fundamental part in the complex and vibrant pattern of intellectual exchange. Reconstructing with any accuracy the importation of Latin or non‐indigenous vernacular texts into any given region is problematic beyond small snapshots of individual collections or booksellers' inventories. Vernacular translations, on the other hand, have left a far more robust record, offering our best opportunity to understand both the depth and nature of interest in other cultures, as well as how ideas were adapted and absorbed. Exploiting recent bibliographical resources, this article examines this surviving record by looking broadly at patterns of vernacular translation in three regions: the Iberian Peninsula, France, and the British Isles. It demonstrates an extraordinary communicative vitality – vernacular translations were highly visible in the early modern marketplace of print. Yet, beyond a common impulse to translate, it is clear that each region exhibited its own very particular tastes and appetites.